PENDAMPINGAN PEMBUATAN BUSINESS MODEL CANVAS PADA USAHA KULINER MBAK NUR DI KABUPATEN SIJUNJUNG, SUMATERA BARAT - Wisnubroto, Muhammad Parikesit; Yulianto, Kiki (Jurnal Abdi Insani, 2024)
Business, Economy, Mentoring, Service, MSMEsCommunity service activities are aimed at transferring and applying science and technology directly to society. This aims to help people's lives improve and develop, including owners of Micro, Small and Medium Enterprises (MSMEs). This community service and assistance was carried out at Mbak Nur's Culinary MSMEs located in Sijunjung Regency, West Sumatra with the theme of creating a Business Model Canvas (BMC). The activity aims to obtain the right business model to support the sustainability of Mbak Nur's Culinary, whose main product is shrimp sweet potato crackers. Apart from that, it is hoped that new ideas will be found to support business development. Activities are carried out in a hybrid manner, namely online and offline. Overall, the implementation of service and mentoring activities for Culinary Mbak Nur was carried out through several stages which included socialization, tutorials, implementation of focus group discussions, direct practice, and evaluation of BMC preparation activities. During the Zoom Meeting, it appeared that MSME owners were enthusiastic about listening to the material presented and the discussion also went well. The results of creating a business model as described previously are felt to be very helpful for shrimp sweet potato cracker business owners in analyzing the business. This business model can also offer new ideas and forms of development, for example in terms of more flexible marketing through digital marketing. Apart from that, BMC also provides business owners with an understanding that running a business requires analysis and modeling which are the basic strategies for developing their business. This program was successful in helping Mbak Nur Culinary develop the nine elements of BMC and determine rational targets related to business development.